IPTEK BAGI MASYARAKAT (IbM) DESA TERONG DAN JATIMULYO DALAM PENGELOLAAN HIPERTENSI DAN DIABETES MELITUS - Dimas Adhi Pradana; Erlina Marfianti; Nita Trimulyaningsih (Asian Journal of Innovation and Entrepreneurship, 2018)
IbM aims to improve the management of hypertension and Diabetes mellitus (DM) through optimizing the Posbindu (Integrated Development Position) Position of Terong and Jatimulyo Villages. The target is the establishment of posbindu with adequate facilities and trained posbindu cadres. Other targets are the formation of IEC media on hypertension and DM and obtaining baseline clinical parameters data and after management for 3 months. Devotion is implemented within 8 months in fiscal year 2017 in cooperation with the government of Terong Village and Jatimulyo and coordinate with local health center that is Dlingo II Public Health Center. The first stage is cadre training and posbindu formation. The training was conducted by using the method of "Learning Active Cadre" (CBKA), cooperative learning, case-based learning with material on Posbindu implementation, risk factor measurement, early detection, hypertension and DM management, herbal treatment, and basic counseling techniques to play motivator healthy lifestyle. After that done early detection (baseline data) and management of hypertension and DM disease for 3 months in order to know the level of improvement of disease management and as a picture of program sustainability. To improve the knowledge of the community also provided IEC media about Posbindu and hypertension and DM. Until the end of October 2017, the Dedication team has completed several programs such as training candidate cadres posbindu, procurement of medical equipment, and the establishment of posbindu in the Village Terong and Jatimulyo. Based on clinical examination data at the opening of posbindu, monitoring and final measurement can be concluded that the implementation of Posbindu has been able to detect, monitor and improve the management of DM patients and hypertension in both villages in order to achieve controlled clinical condition.